DEVELOPING BIG BOOK AS A MEDIA FOR TEACHING ENGLISH AT SIXTH GRADE STUDENTS OF ELEMENTARY SCHOOL AT SD LAB UNDIKSHA SINGARAJA - Mahayanti, Ni Wayan Surya; Suantari, Ni Luh Putu Mira (LPPM Undiksha, 2017)
This research aimed to (1) develop character based big book as a media for teaching English at sixth grade students at SD Lab UNDIKSHA Singaraja, and (2) find out the quality of character based big book developed. The subject of this research was thirty-two students of sixth grade students of elementary school at SD Lab UNDIKSHA Singaraja. The data of this research were obtained by using observation sheet, interview guide, item of questionnaire, checklist, rubric, and notes. This research was R & D (research and development) which followed several procedures based on Sugiyono model namely identifying potency and problem, collecting data, designing product, validating design product, revising design product, trying-out product, and revising product. The result of this research showed that there were five kinds of character based big book developed with the theme seasons, tourism, direction, airport, and transportation. Each big book consisted of fourteen up to fifteen pages and inserted character education in its story. For the quality of the media, it was found that the character based big book developed was categorized as excellent media. Thus, it was proper to be used as a media for teaching English at sixth grade students.